THE MAIN PSYCHOLOGICAL AND PEDAGOGICAL REQUIREMENTS OF INFORMATICS TEXTBOOKS FOR 6TH - Popel M.; Borysiuk I. (Kherson State University, 2017)
In the article the psychological characteristics of pupils 6th grade: rapid psychophysical development and crises inherent in early adolescence. For a comparative analysis of knowledge of pupils as the fifth and sixth grades by training years (2013-2014, 2014-2015) the dependence of quality of knowledge from the problems of adolescence. The specifics of semantic informatics textbooks for 6th grade is taking into account the age and characteristics of pupils need reflected on the psychological and educational requirements. Presents the basic functions performed by the textbook as a teaching tool, particularly in informatics. Considered the requirements set by the modern informatics textbook T. P. Sokolowski. Analysis of current informatics textbooks for 6th grade on the example of studying the topic "Algorithms and their performers' and found some problems in their content. Considering completed research were summarized and singled the basic psychological and pedagogical requirements to be met by informatics textbooks for 6th grade. As the prospects for further research appears analysis electronic editions of informatics and refinement requirements for defined existing textbooks considering psychological characteristics of young adolescents.